Effect of Urea, NPK and Compost on Growth and Yield of Soybean (Glycine max L.), in Semi-Arid Region of Sudan. (29th February 2012) - Yagoub, Samia Osman; Ahmed, Wigdan Mohamed Ali; Mariod, A. A.
Abstract : A field experiment was conducted for two consecutive seasons (2009/2010 and 2010/2011) on the Demonstration Farm of the College of Agricultural Studies, Sudan University of Science and Technology at Shambat, to study the effect of some fertilizers on growth and yield of soybean ( Glycine max L. merril ). The experiment was laid out in a randomized complete block design (RCBD) with four replicates. The fertilizers treatments consisted of three types of fertilizers: urea (180 kg/ha), NPK (361 kg/ha), compost (%) and the control. The results showed that fertilizers treatments in first season had significant difference on number of pods/plant, economic yield, harvest index. Mean while, highly significant difference on green, biological and straw yield. In second season fertilizers treatments had significant difference on plant height at 30 days, leaf area at 45 and 60 days, green yield, biological yield and straw yield.